2012
DOI: 10.1186/1471-2458-12-858
|View full text |Cite
|
Sign up to set email alerts
|

A one-year observational study of all hospitalized and fatal acute poisonings in Oslo: Epidemiology, intention and follow-up

Abstract: BackgroundUp to date information on poisoning trends is important. This study reports the epidemiology of all hospitalized acute poisonings in Oslo, including mortality, follow-up referrals, and whether the introduction of over-the-counter sales of paracetamol outside pharmacies had an impact on the frequency of poisonings.MethodsAll acute poisonings of adults (≥16 years) treated at the five hospitals in Oslo from April 2008 to April 2009 were included consecutively in an observational cross-sectional multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 25 publications
8
37
1
7
Order By: Relevance
“…In the present study, psychoactive pharmaceutical products were the main toxic agent in only 7% of in-hospital and 16% of pre-hospital deaths. According to the present results, the causes of pre-hospital deaths related to pharmaceutical products have similar characteristics as hospital survivors reported in studies from Norway reporting a predominance of opioid and psychoactive pharmaceutical drugs [1, 7]. In the present study, these agents were involved in nearly one-third of pre-hospital deaths and only every sixth in-hospital death.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, psychoactive pharmaceutical products were the main toxic agent in only 7% of in-hospital and 16% of pre-hospital deaths. According to the present results, the causes of pre-hospital deaths related to pharmaceutical products have similar characteristics as hospital survivors reported in studies from Norway reporting a predominance of opioid and psychoactive pharmaceutical drugs [1, 7]. In the present study, these agents were involved in nearly one-third of pre-hospital deaths and only every sixth in-hospital death.…”
Section: Discussionsupporting
confidence: 87%
“…Nearly half (42%) of patients received the activated charcoal more than 2 hours after exposure to toxins. A Norwegian study reported 16% activated charcoal use for all admitted acute-poisoning patients in Oslo [34, 35]. However, our study also showed a low mortality rate in both the charcoal-available and charcoal-unavailable periods.…”
Section: Discussionsupporting
confidence: 40%
“…Norveç'te(28) yapılan çalışmada %0.8 oranında zehirlenmelere bağlı ölüm görülmüştür. Ülkemizde yapılan çalışmalarda akut intokikasyonlara bağlı zehirlenmelerde mortalite %0.9-%9.1 arasında değiştiği saptandı (16,19,22,23,28 …”
Section: Introductionunclassified